Efficient Monte Carlo Procedures for Generating Points Uniformly Distributed over Bounded Regions - Smith, Robert L. (Operations Research, 1984)
We consider the Monte Carlo problem of generating points uniformly distributed within an arbitrary bounded (measurable) region. The class of Markovian methods considered generate points asymptotically uniformly distributed within the region. Computational experience suggests the methods are potentially superior to conventional rejection techniques for large dimensional regions.